Techno-economic analysis on a new conceptual design of waste heat recovery for boiler exhaust flue gas of coal-fired power plants. (15th November 2019) - Jin, Yunli; Gao, Naiping; Zhu, Tong
Highlights: Contradiction in LPE between heat recovery rate and utilized efficiency is analyzed. Contradiction in LPE is resolved by converting recovery heat. Recovery heat is converted by organic fluid cycle integrating ORC with HTHP. Efficiency improvement upper limit by heat conversion is obtained by exergy analysis. Techno-economic analysis and thermodynamic optimization are carried out. Abstract: Recovering waste heat from boiler exhaust flue gas is an effective way to improve energy utilization efficiency and reduce coal burning pollution of coal-fired power plant (CFPP). The low-pressure economizer (LPE) is the most widely employed in waste heat recovery from boiler exhaust flue gas. However, there is a contradiction in LPE between maximizing waste heat recovery rate and maximizing waste heat utilization efficiency. This research improves waste heat utilization efficiency without reducing recovery rate by converting recovery heat. The recovery heat conversion is realized through organic fluid cycle integrating organic Rankine cycle (ORC) with high temperature heat pump (HTHP). The organic fluid cycle acts as a medium between flue gas and feedwater, which makes recovery heat match higher parameter low-pressure heater (LPH) flexibly. Based on exergy analysis, the upper limit for elevating energy-saving effects by converting recovery heat is given. For calculations and analyses, thermodynamic models are built and simulated in MATLAB together with REFPROP software based on a case study. The results show that using the proposed waste heat recovery system could produce 5361.98 kW additional net power output and electricity revenue of 1220.04 k, which are approximately 409.19 kW and 127.2 k greater than LPE respectively. The proposed system could save 5699.36 t standard coal and 854.9 k coal cost per year, which are nearly 595.5 t and 89.32 k larger than LPE. The maximum of recovery heat utilization efficiency of proposed system reaches 17.35% and the maximum efficiency improvement compared to LPE touches 3.48%.